Artikulasi Politik Dan Kepentingan Partai Politik: Dalam Perspektif Fiqhu al-siyâsah - Hamdani (Jurnal Risalah Hukum, 2006)
Political practice of political parties and all politicians in this time tend to be dominated by action and activity allowing all kinds of way, this matter will get legitimation based on political principal which express there is no closed friend or endless friend besides it has interest endless, so that the conflict of ideology among the parties is not a hindrance to be united as long as there is the same interest, that way on the contrary if the interests among them have differed hence committing of political treason is a matter which is regarded valid to be conducted, this practice ending by giving the stigma that politics is a dirty matter. Part of primal thing in understanding the politician behaviour is when we understand that the politician is a human that having the thinking potential, therefore he/she has the certain understanding of politics, thus it becomes the basis of political activities for him/her. Based on this measured point, we understand that the root of mistake or error of inconsistent activity and the frequently destructive character in political activity is inexistence of good understanding, correctness and constructive about politics itself. How can it have the character of constructive and give the best service benefit for the sake of people if politics itself defined to something that has the character of power starving in the framework of needs fulfillment which is relied on materialism such as honor, income, and security or safety based on human being desire even will never come up with satisfaction boundary. Key words: politik (politic), kekuasaan (power), negara (state), ideologi (ideology).